Accessible Environment for Young People with Disabilities in St Petersburg: Sociological Analysis - O. A. Novozhilova (Дискурс)
Introduction. The article is devoted to the opportunities and barriers of the environment. It is proposed to look at the creation of an “accessible environment” not only as the elimination of physical barriers, but also from the point of view of its possibilities for the inclusion of people with disabilities in public life. The purpose of the article is to assess the possibilities of the environment and identify the levels of interaction with the environment for young people with disabilities. The scientific novelty of the study is there are many levels of the environment when we talk about people with disabilities.Methodology and sources. Based on the ecological theory of the social psychologist W. Bronfenbrenner, the levels of the environment are divided into micro, meso, and macro levels. However, this is only a vertical division of levels. The environment is perceived by individuals much more broadly. The empirical part of the work is represented by a qualitative methodology, a semi-structured interview (N = 18) was conducted with young people with visual impairment and musculoskeletal disorders. The full picture of the study was complemented by expert interviews (N = 3) with representatives of public organizationsResults and discussion. There are horizontal levels of the environment, namely the physical environment, media space, and social interaction. As well as vertical levels, which include family, education, employment. Some levels have sub-levels, in each of which there are certain environmental barriers. The interaction of young people with disabilities with the environment at each of these sublevels will be different.Conclusion. An accessible environment is an opportunity for a young person with disabilities not only to go beyond their home, but also to be a full-fledged member of society, an active participant in social relations; the opportunity to express oneself, to be heard; as well as the opportunity to realize your identity and self-realization.